Relationality and complementarity in the children and youth stories of “El socavón plateado. cuentos y relatos mineros” of Wanca Willca - Bautista, María José (2021)
The purpose of the work will be to identify the relationality and complementarity categories in the Miners’ Tales and Stories by Wanca Willca, an author from Jujuy. The book consists of stories that could be defined as children’s and juvenile ones telling stories, in which there are not always happy endings, set in the bloody mine environment.By applying the relationality and complementarity categories the essay will set out the identification, in the stories, of two ways of dealing with that violence. The first will be focused from the perspective of man’s relationality with his surrounding, from the protection provided by the huacas or tutelary gods that help and restore balance. A second orientation will be from the predominant role of the community, the complementarity with the other as the nucleus of saving action and only resource of liberation.